The use of animal models to discover immunological mechanisms underpinning sensitization to food allergens. (2015) - Smit, Joost J.; Noti, Mario; O'Mahony, Liam
Abstract : In almost all countries, food allergy is of growing concern affecting all age groups. Given the increased prevalence of food allergies, current research focuses on developing new treatment strategies and to predict allergenicity of novel and modified food proteins. The recent use of animal models has significantly contributed to a better understanding of the complex immunological and pathophysiological mechanisms of food allergies. Central to the development of food allergy is the allergic cascade driven by cells of the innate and adaptive immune system. These models can now be integrated into the risk assessment of possible allergenic proteins. In this review, we discuss the role of the immune system as a qualitative readout for the sensitizing potential and risk assessment of food proteins.